β-Caryophyllene/Hydroxypropyl-β-Cyclodextrin Inclusion Complex Improves Cognitive Deficits in Rats with Vascular Dementia through the Cannabinoid Receptor Type 2 -Mediated Pathway - Lou, Jie; Teng, Zhipeng; Zhang, Liangke; Yang, Jiadan; Ma, Lianju; Wang, Fang; Tian, Xiaocui; An, Ruidi; Yang, Mei; Zhang, Qian; Xu, Lu; Dong, Zhi (Frontiers in Pharmacology, 2017)
This work was conducted to prepare β-caryophyllene-hydroxypropyl-β-cyclodextrin inclusion complex (HPβCD/BCP) and investigate its effects and mechanisms on cognitive deficits in vascular dementia (VD) rats. First, HPβCD/BCP was prepared, optimized, characterized and evaluated. HPβCD/BCP and AM630 were then administered to VD rats to upregulate and downregulate the cannabinoid receptor type 2 (CB2). Results showed that HPβCD/BCP can significantly increase the bioavailability of BCP. Through the Morris water maze test, HPβCD/BCP can attenuate learning and memory deficits in rats. Cerebral blood flow (CBF) monitoring results indicated that HPβCD/BCP can promote the recovery of CBF. Moreover, molecular biology experiments showed that HPβCD/BCP can increase the expression levels of CB2 in brain tissues, particularly the hippocampus and white matter tissues, as well as the expression levels of PI3K and Akt. Overall, the findings demonstrated the protective effects of HPβCD/BCP against cognitive deficits induced by chronic cerebral ischemia and suggested the potential of HPβCD/BCP in the therapy of vascular dementia in the future.